ETHNIC CONCENTRATION AREAS IN NEIGHBOURHOOD PERSPECTIVE IN ENSCHEDE, THE NETHERLANDS - Rian Wulan; Javier Martinez; Sherif Amer (Indonesian Journal of Geography, 2013)
Previous studies suggest that measuring ethnic segregation at a disaggregated level allows capturing variabilityof ethnic concentration areas within a city. However, many ignore the relative locations of each neighbourhoodto identify ethnic concentration areas. It causes misidentification of ethnic concentration areas. Using the 2009population data of Enschede, this study investigated the concentration areas at postcode level. The “scale of theneighbourhood” represents the extent of concentration influenced by population in neighbouring postcodes.Using composite population at different scales of neighbourhood, it was revealed that concentration areas atsub-city level are characterized by isolation and clustering dimensions. Few postcodes are Turkish or Moroccanconcentration areas which are located outside the city center. Small number of cluster and isolated areaindicates that the ethnic concentration in Enschede is relatively low. The study has advanced the hypothesisabout segregation measurement, that spatial proximity to neighbouring areas has a large impact on variabilityof ethnic segregation.